Factors influencing individuals' trust in online purchase through social networking sites - Nor, K. M. (2013)
Internet is integrated into nearly all aspects of activities including businesses. It is a medium that can be accessed anywhere. The advancement of Internet has contributed to the development of electronic commerce and trust has been suggested in the literature to play an essential role in the development of e-commerce. Lately, e-commerce has also taken placed in a new platform, Social Networking Sites (SNSs). As in e-commerce, individuals' trust is also important in using SNSs as the medium of commerce. Based on literature review, we found limited number of studies investigating factors that affect individuals' trust in this medium. Examining factors that influence individuals' trust in online purchase using SNSs was the primary concern of this research. In this study, four factors were examined which are propensity to trust, experience in online purchase, testimonial, and monetary risk. The samples of this research were 129 Facebook users. Questionnaires were distributed through email and a posting on the researcher's Facebook. Multiple regression analysis was used to test the relationships proposed in the study. The study revealed that propensity to trust and testimonial were two significant factors that influence individuals' trust in online purchase through SNSs.